Training possibilties in Europe; newsletter - Organisation for Economic Co-operation and Development; Organization for European Economic Cooperation (Paris : Organization for European Economic Cooperation., 1962)
This book examine a wide variety of training facilities particularly suitable for people from developing countries. The training offered include: agriculture and natural resources, industry and mining, transportation, labour, Health and sanitation Education among others.
Serial.
usc 22/01/2019
Loans
Keywords: Technical assistance, American; Vocational education; Organisation for Economic Co-operation and Development; Technical assistance; Europe; Developing countries